Detection of alpha(0)-thalassemia South-East Asian-type deletion by droplet digital PCR - Pornprasert S. (2014)
Background: The α(0)-thalassemia South-East Asian (SEA)-type deletion is the most common genetic disorder in the Asian population. Couples who are both carriers have a 25% chance of conceiving Bart's hydrops fetalis. Therefore, results from carrier screening and prenatal diagnosis frequently need to be available rapidly. The aim of this study was to implement a droplet digital polymerase chain reaction (ddPCR) for diagnosis of α(0)-thalassemia SEA-type deletion. Methods: The wild-type α-globin gene allele and α(0)-thalassemia SEA allele were quantified in DNA samples of 20 normal individuals, 15 samples with α(0)-thalassemia SEA trait, and 8 samples with Bart's hydrops fetalis using the ddPCR. The DNA copy number of wild-type α-globin gene allele and α(0)-thalassemia SEA allele was then calculated using the Quantasoft analysis software. Results: The mean ± standard deviation (SD) ratio of wild-type α-globin gene allele and α(0)-thalassemia SEA allele among normal individuals, samples with α(0)-thalassemia SEA trait, and Bart's hydrops fetalis were clearly distinguished with levels of 1.78 ± 0.49, 0.85 ± 0.14, and 0.03 ± 0.03, respectively. Conclusion: The ddPCR may be one alternative technology available for routine clinical diagnosis of α(0)-thalassemia SEA-type deletion and prenatal diagnosis of Bart's hydrops fetalis. © 2013 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd.